COVID-19 y su trascendencia en la atención dental: revisión y actualización de la literatura - Mija Gómez, Jorge Luis (2020)
By the end of 2019, 27 atypical pneumonia cases of unknown etiology were presented in Wuhan, China. The symptoms of the patients suffering from the new viral pneumonia were fever, dry cough, dyspnea, and fatigue. The virus was named coronavirus type 2 causing severe acute respiratory syndrome (SARS-CoV-2) and the disease was named in February 2020 by the World Health Organization as coronavirus disease COVID-19. The routes of transmission from person to person include direct transmission by inhalation of cough droplets, sneezing, and indirect transmission, through fomites that contact the oral, nasal, or ocular mucous membranes. Dentists, due to the unique nature of the procedures they perform, have a high risk of COVID-19 cross-infection, since when working in the patient's mouth they are exposed to a large number of saliva drops and aerosols that are produced during dental treatments. The COVID-19 pandemic requires dentists with special preparation for the prevention of contagion in the dental office. The dentist should also be updated on how COVID-19 relates to the profession to be well prepared and to be an active member in sanitary measures to control the pandemic. This review aims to present updated information on COVID-19 and to provide scientific support for the use of different strategies to minimize the risk of cross-contamination in dental practice during the COVID-19 pandemic.